Per rectal portal scintigraphy as a useful tool for predicting esophageal variceal bleeding in cirrhotic patients - Chitapanarux T. (2014)
Aim: To investigate potential roles of per rectal portal scintigraphy in diagnosis of esophageal varices and predicting the risk of bleeding. Methods: Fifteen normal subjects and fifty cirrhotic patients with endoscopically confirmed esophageal varices were included. Patients were categorized into bleeder and non-bleeder groups according to history of variceal bleeding. All had completed per rectal portal scintigraphy using 99mTechnetium pertechnetate. The shunt index was calculated from the ratio of 99mTechnetium pertechnetate in the heart and the liver. Data were analyzed using Student's t-test and receiver operating characteristics. Results: Cirrhotic patients showed a higher shunt index than normal subjects (63.80 ± 25.21 vs 13.54 ± 6.46, P < 0.01). Patients with variceal bleeding showed a higher shunt index than those without bleeding (78.45 ± 9.40 vs 49.35 ± 27.72, P < 0.01). A shunt index of over 20% indicated the presence of varices and that of over 60% indicated the risk of variceal bleeding. Conclusion: In cirrhotic patients, per rectal portal scintigraphy is a clinically useful test for identifying esophageal varices and risk of variceal bleeding. © 2007 The WJG Press. All rights reserved.